Peran Akreditasi Sekolah dalam Meningkatkan Promosi Sekolah di MI Ciawitali 01 - Nurasiah Jamil; Siti Qomariyah; Do’a Fajarwati (Universitas 45 Surabaya, 2025)
The aim of this research is to analyze the role of school accreditation in improving school promotion in Mi Ciawitali 01. This research was conducted using a qualitative methodology that collected data through observation, interviews and documentation. The data analysis techniques used include data reduction, data delivery, data verification, and drawing conclusions. The results of this research include the Implementation of Accreditation at Mi Ciawitali 01, the Role of Accreditation in Increasing School Promotion at Mi Ciawitali 01, Inhibiting and Supporting Factors for Implementing Accreditation at Mi Ciawitali 01.